THE CORRELATION BETWEEN STUDENTS’ HABIT IN WATCHING ENGLISH MOVIE AND LISTENING ACHIEVEMENT (BY FOURTH SEMESTER STUDENTS OF UNIVERSITAS MUHAMMADIYAH PALEMBANG) - Rositasari, Tri; Larasati, Finza; Yunensi, Yunensi (Universitas Muhammadiyah Palembang, 2019)
The objective of this study was to find out the correlation between students’ habit in watching English movie (X) and listening achievement(Y) by fourth semester students of Universitas Muhammadiyah Palembang There were 47 students taken as the sample of this study who were determined by using purposive sampling technique. The collected data was analyzed by using Pearson Product Moment Correlation and the instruments used were students’ listening scores and questionnaire of students’ habit in watching English movie. Subsequently, the research finding indicated that there was low correlation between students’ habit in watching English movie and listening achievement. It proved by the obtain (0.212) which lower than r table (0.2845). It considered that alternative hypothesis (Ha) in this research was rejected and the null hypothesis (Ho) which stated that there was no correlation between students’ habit in watching English movie and their listening achievement accepted. In conclusion, there was low correlation between students’ habit in watching English movie and their listening achievement.